2016
DOI: 10.4238/gmr.15028150
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid upregulates ERK and Akt in the protection of cardiomyocytes against CoCl2

Abstract: ABSTRACT. Ursodeoxycholic acid (UDCA) is used to treat liver diseases and demonstrates cardioprotective effects. Accumulation of the plasma membrane sphingolipid sphingomyelin in the heart can lead to atherosclerosis and coronary artery disease. Sphingomyelinases (SMases) break down sphingomyelin, producing ceramide, and inhibition of SMases activity can promote cell survival. We hypothesized that UDCA regulates activation of ERK and Akt survival signaling pathways and SMases in protecting cardiac cells agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Previously, we have reported that UDCA protects CMs against hypoxia induced by CoCl 2. While in here, we show the difference in the cardioprotection effects of UDCA given prior to hypoxia induction (pre‐UDCA) with CMs posttreated with UDCA after hypoxia induction (post‐UDCA). Our findings suggested similar protection of UDCA either given before or after hypoxia in cell viability and HIF‐1α protein activity.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Previously, we have reported that UDCA protects CMs against hypoxia induced by CoCl 2. While in here, we show the difference in the cardioprotection effects of UDCA given prior to hypoxia induction (pre‐UDCA) with CMs posttreated with UDCA after hypoxia induction (post‐UDCA). Our findings suggested similar protection of UDCA either given before or after hypoxia in cell viability and HIF‐1α protein activity.…”
Section: Discussionmentioning
confidence: 55%
“…In hepatocytes, UDCA activates various cell signalling pathways such as p53 and S1P receptor via Gα i ‐coupled receptor . Recently, our group has reported that UDCA protects CMs against chemically induced hypoxia through ERK, AKT, and ROS activity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticholestatic, choleretic and litholytic effects of UDCA stipulate the main usage of this drug, namely, therapy of cholestasis, cholelithiasis, hepatitis, liver cirrhosis. But it was revealed that UDCA has a much wider spectrum of action because of its cytoprotective, anti-apoptotic, anti-inflammatory, antioxidative and immune-modulating effects, which are of especial value in cardiology [8,18,19].…”
mentioning
confidence: 99%
“…This leads to membrane stabilization and increases cell resistance to various damages [13], which is especially important for protection against xenobiotics' action. UDCA also increases cardiomyocytes' resistance to hypoxia [19]. Anti-apoptotic effect of UDCA is provided mainly by decrease of Са 2+ concentration in the cells, prevention of cytochrome C exit from the mitochondria, decrease of caspases' activation [12,13].…”
mentioning
confidence: 99%